Parity bifurcations in trapped multistable phase locked exciton-polariton condensates - Tan, E. Z. (2018)
We present a theoretical scheme for multistability in planar microcavity exciton-polariton condensates under nonresonant driving. Using an excitation profile resulting in a spatially patterned condensate, we observe organized phase locking which can abruptly reorganize as a result of pump induced instability made possible by nonlinear interactions. For π/2 symmetric systems this reorganization can be regarded as a parity transition and is found to be a fingerprint of multistable regimes existing over a finite range of excitation strengths. The natural degeneracy of the planar equations of motion gives rise to parity bifurcation points where the condensate, as a function of excitation intensity, bifurcates into one of two anisotropic degenerate solutions. Deterministic transitions between multistable states are made possible using controlled nonresonant pulses, perturbing the solution from one attractor to another.